Thyroid profile in patients with breast tumors - V.G.KARPAGHAVALLI,; S.SUMATHY,; PRAGNA B DOLIA, (International Journal of Pharma and Bio Sciences, 2016)
Most breast carcinoma are hormone dependent. Two-thirds of breast cancers have estrogen or progesterone receptor positivity. Conflicting results regarding the clinical correlation between breast carcinoma and thyroid diseases have been reported. The objective of this study was to determine the thyroid profile in patients with newly diagnosed benign and malignant breast tumors. Serum samples were collected from 30 female patients with newly diagnosed breast carcinoma having FNAC report as ductal cell carcinoma and 28 female patients with newly diagnosed benign breast tumors having FNAC report as fibroadenoma or fibroadenosis. Serum samples were analyzed for TSH, free T4and free T3 levels. 30 age matched normal healthy controls were also examined for the same parameters. Breast carcinoma patients had raised serum TSH levels and low freeT4 and freeT3 levels compared to controls and benign breast tumor patients. There was a significant association between thyroid hypofunction and breast carcinoma.